Combining ability analysis in okra (Abelmoschus esculentus (L.) Moench) - Kumar, Prashant; Singh, Vikas; Dubey, RK (Vegetable Science, 2012)
In any crop improvement programme, the proper choice of parents based on their combining ability is a prerequisite. The knowledge of combining ability helps in identifying best combiners, which may be hybridized either to exploit heterosis or to accumulate fixable genes through selection. The general and specific combining ability in respect of a character is the manifestation of additive and non-additive gene action, respectively. The line x tester analysis is one of the most useful techniques for preliminary evaluation of genotypes for use in hybridization programmes with a view to identify good combiners. In okra, studies on this aspect have been made by several workers elsewhere (Pathak et al., 1998 and Yadav et al., 2002). But such information which forms a back bone of any breeding programme is very meagre. Therefore, an attempt has been made to study the combining ability for 13 characters by line x tester mating design as suggested by Kempthorne (1957).